Service Quality and Facilities on Satisfcation Through Individual Emotional for Bpjs Participants in Sinjai District - Nurlaela, Nurlaela; Syarifuddin, Umar; Liong, Harlina; Munawwarah, Rofiqah Al (Vifada Management and Social Sciences, 2024)
This research aims to analyze product innovation and marketing strategies implemented by Bundang's Sweet and Sour Candy MSMEs to increase competitiveness in the market. The research method used is descriptive qualitative with data collection through interviews, observation and documentation studies. The research results show that product innovation, such as the development of more attractive flavor variants and packaging, contributes significantly to increasing consumer interest. On the other hand, digital-based marketing strategies through social media and marketplaces have also succeeded in expanding market reach. With a combination of product innovation and effective marketing, these MSMEs are able to compete with similar products and increase market share. This research recommends strengthening the synergy between product innovation and marketing as the key to success in facing increasingly fierce competition